Visual analysis based on CiteSpace software: a bibliometric study of atrial myxoma - Gao, Ang; Yang, Jinghua; Tian, Tongru; Wu, Yang; Sun, Xiaoting; Qi, Na; Tian, Nan; Wang, Xian; Wang, Jisheng (Frontiers in Cardiovascular Medicine, 2023)
Objective: To use CiteSpace and VOSviewer visual metrology to analyze the research status, frontier hotspots, and trends in research on atrial myxoma. Methods: The Web of Science core collection database was used to retrieve relevant literature on atrial myxoma from 2001 to 2022. CiteSpace software was used to analyze keywords with a co-occurrence network, co-polymerization class, and burst terms, and a corresponding visual atlas was drawn for analysis. Results: A total of 893 valid articles were included. The country with the highest number of articles was the United States (n=186). The organization with the highest number of articles was the Mayo Clinic (n=15). The author with the highest number of articles was Yuan SM (n=12). The highest cited author was Reynen K (n=312). The highest cited journal was Annals of Thoracic Surgery (n=1067). The most frequently cited literature was published in the New England Journal of Medicine in 1995, which was cited 233 times. The keywords co-occurrence, copolymerization analysis, and Burst analysis revealed that the main research focuses were surgical methods, case reports, and genetic and molecular level studies on the pathogenesis of myxoma. Conclusions: Surgical methods, case reports, and genetic and molecular studies on atrial myxoma are current research hotspots. Frontier research includes the application of minimally invasive surgery and the development of new targeted drugs, which are possible future development directions in the field of atrial myxoma.